Silence of the Limbs: Pharmacological Symptomatic Treatment of Intermittent Claudication - De Backer, Tine; Vander Stichele, Robert; De Buyzere, Marc; De Backer, Guy; Van Bortel, Lucas (Current Vascular Pharmacology, 2010)
Several oral “vasoactive” drugs claim to increase walking capacity in patients with intermittent claudication (IC). Naftidrofuryl, cilostazol, buflomedil, and pentoxifylline are the most studied molecules. Although spanning several decades, several studies underlying these claims were not properly designed, underpowered or showed clinically doubtful outcomes. The evidence for these “vasoactive” drugs has always been received with scepticism, creating the need for systematic reviews and meta-analyses. This brief review discusses the benefit-risk assessment of vasoactive drugs, by applying a systematic review to evaluate randomized, placebo-controlled trials. Oral naftidrofuryl and cilostazol have an acceptable safety profile as well as sustained evidence (documented by Cochrane analyses) of increased walking capacity. Subsequently, these drugs entered recommendations for peripheral arterial disease (PAD). In contrast, buflomedil and pentoxifylline have limited and/or doubtful evidence to increase walking capacity. Moreover, there were safety concerns about the narrow therapeutic range of buflomedil. Most other “vasoactive” drugs were either inappropriately or insufficiently tested or showed no significant if not negative effects on IC. “Vasoactive” drugs are no substitutes for lifestyle or exercise therapy but are adjuvant treatment to the well-appreciated triad of cardiovascular prevention (antiplatelet agents, statins and ACE-inhibitors), of which statins in their own right have documented claims to significantly increase walking capacity. “Vasoactive” drugs may have a place in the pharmacological management of symptomatic PAD in addition to the basic cardiovascular pharmacotherapy, when revascularization is not indicated, when exercise therapy is not feasible or when there is still insufficient benefit.
Keywords: naftidrofuryl